A kind of stone crystal negative ion plate and preparation method thereof

By using modified polyvinyl chloride, modified bamboo and wood fibers in stone crystal negative ion sheets, combined with composite flame retardant and modified tourmaline powder, a plate with high mechanical properties and negative oxygen ion release function was prepared, which solved the problem of poor mechanical properties of the sheets and inability to release negative oxygen ions in the prior art.

CN118994811BActive Publication Date: 2025-04-29JIANGXI LONGCHEN TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411079059.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2025-04-29
Estimated Expiration
2044-08-07

AI Technical Summary

Technical Problem

In the prior art, the mechanical properties of stone crystal negative ion sheets are poor and cannot release negative oxygen ions, which cannot meet the requirements of modern buildings and home decoration for materials improvement.

Method used

The modified polyvinyl chloride, modified bamboo and wood fiber, composite flame retardant components, modified tourmaline powder, calcium carbonate, barium zinc stabilizer, oxidation wax, polyethylene wax, foaming agent and foaming regulator are blended in a high-speed mixer, and stone crystal negative ion plates are prepared through the extrusion mechanism.

Benefits of technology

It realizes the high strength, high toughness and excellent wear resistance of the plate, and also has the function of continuously releasing negative oxygen ions, improving indoor air quality and extending service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004983196120000111
    Figure BDA0004983196120000111
  • Figure BDA0004983196120000112
    Figure BDA0004983196120000112
Patent Text Reader

Abstract

The invention relates to the technical field of polymer plates, and in particular to a stone crystal negative ion plate and a preparation method thereof. The invention comprises the following steps: coating bamboo wood fibers with titanium dioxide and copper oxide to prepare modified bamboo wood fibers, and then adding the modified bamboo wood fibers into modified polyvinyl chloride to prepare negative ion plates. The prepared negative ion plates can generate negative oxygen ions under light, and have the ability to continuously generate negative oxygen ions. Titanium dioxide is a material with photocatalytic activity. Under the irradiation of ultraviolet light or visible light, it can be excited to generate electrons and holes, so that they react with water molecules and oxygen in the air to generate hydroxyl free radicals and superoxide anions with strong oxidizing properties, which are then converted into negative oxygen ions. Copper oxide and titanium dioxide can form a composite system, and the overall photocatalytic efficiency can be improved through synergistic effect, thereby promoting the generation of negative oxygen ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer plates, and in particular to a stone crystal anion plate and a preparation method thereof. Background Art

[0002] With the rapid development of modern construction and home decoration industry, the requirements for decoration materials are increasing day by day, especially in terms of mechanical properties, flame retardant properties and environmental health. Polyvinyl chloride, as a widely used plastic material, is known for its good processability, weather resistance and mechanical strength. Stone crystal anion sheet with polyvinyl chloride as the main base material has achieved high strength, high toughness and excellent wear resistance through scientific formula design and advanced production technology. This kind of sheet can maintain a stable structural form when subjected to daily use and heavy pressure, and is not easy to deform or damage, which effectively extends the service life.

[0003] Negative ions are known as "air vitamins" and have a significant promoting effect on human health. They can promote human metabolism, enhance immunity, improve sleep quality, etc. Through innovative preparation technology, the stone crystal negative ion board combines materials with negative ion release function with polyvinyl chloride materials to achieve the continuous release of negative oxygen ions. These negative ion materials form a stable microstructure inside the board, effectively combine with oxygen in the air, and generate high concentrations of negative oxygen ions, thereby improving indoor air quality and creating a healthy and comfortable living environment. Summary of the invention

[0004] Technical issues solved

[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a stone crystal negative ion plate and a preparation method thereof, which can effectively solve the problem that the plate of the prior art has poor mechanical properties and cannot release negative oxygen ions.

[0006] Technical Solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A stone crystal anion plate, the stone crystal anion plate is composed of the following components: modified polyvinyl chloride, modified bamboo fiber, composite flame retardant component, modified tourmaline powder, calcium carbonate, barium zinc stabilizer, oxidized wax, polyethylene wax, foaming agent and foaming regulator, the foaming agent is azodicarbonamide;

[0009] The modified polyvinyl chloride is prepared by toughening and modifying polyvinyl chloride with acrylic rubber and ethylene-vinyl acetate copolymer;

[0010] The modified bamboo fiber is prepared by coating the bamboo fiber with titanium dioxide and copper oxide;

[0011] The composite flame retardant component is prepared by mixing nanometer calcium hydroxystannate, aluminum oxide, zinc oxide and nanometer silicon dioxide;

[0012] The modified tourmaline powder is obtained by modifying tourmaline powder with a silane coupling agent.

[0013] Furthermore, the preparation method of the modified polyvinyl chloride is: weigh 55-60g of polyvinyl chloride, 6-7g of acrylic rubber, 7-8g of ethylene-vinyl acetate copolymer and 5-8g of silane coupling agent KH-560, pour them into a high-speed mixer, blend them at a temperature of 110-120°C and a stirring speed of 500-600r / min for 10 minutes, and the resulting modified polyvinyl chloride is obtained.

[0014] Furthermore, the preparation steps of the modified bamboo fiber are:

[0015] Step 1, weigh 2-3g of ammonium fluorotitanate and 2-3g of boric acid and disperse them in 150-200g of deionized water, stir and dissolve them, pour them into a reaction kettle together with 18-20g of bamboo fiber, react at 90°C for 5h, cool to room temperature, then rinse with deionized water and dry at 45°C for 6h, the obtained product is recorded as pre-modified bamboo fiber;

[0016] Step 2: Weigh 1-2g of polyvinyl pyrrolidone and 3-4g of glucose and add them to 25-30g of copper acetate solution. After stirring and dispersing, pour them into the reactor together with 18-20g of pre-modified bamboo fiber. React at 180°C for 2h and then cool to room temperature. Then rinse with deionized water and dry at 45°C for 6h to obtain modified bamboo fiber.

[0017] Furthermore, the specific operation of stirring and dissolving in step 1 is stirring at a stirring speed of 500 r / min for 30 min, the concentration of the copper acetate solution in step 2 is 0.1 mol / L, and the specific operation of stirring and dispersing in step 2 is stirring at a stirring speed of 300 r / min for 1 h.

[0018] Furthermore, the preparation steps of the nano calcium hydroxystannate are:

[0019] Step 1, weigh 1g of anhydrous calcium chloride, add it into a flask filled with 1L of deionized water, stir until dissolved, and record the result as the calcium chloride component; weigh 3g of sodium stannate trihydrate, add it into a flask filled with 1L of deionized water, stir until dissolved, and record the result as the sodium stannate hydrate component;

[0020] Step 2: Add 80-90 mL of triethylamine to 100 mL of the hydrated sodium stannate component, mix well, then add 100 mL of the calcium chloride component at a rate of 1 drop / s, and let the reaction stand at room temperature for 3-4 hours. The resulting precipitate product is washed 3 times with anhydrous ethanol and deionized water, then freeze-dried for 12 hours to obtain nano-hydroxy calcium stannate.

[0021] Furthermore, the specific operation of stirring until dissolved in step 1 is stirring at a stirring speed of 500 r / min for 10 min, and the specific operation of mixing evenly in step 2 is stirring at a stirring speed of 300 r / min for 10 min.

[0022] Furthermore, the preparation method of the composite flame retardant component is: weigh nano-hydroxy calcium stannate, aluminum oxide, zinc oxide, nano-silicon dioxide and silane coupling agent KH-570 according to a weight ratio of 3:2:1:2:1, pour them into a ball mill for ball milling, and the composite flame retardant component is obtained after ball milling for 10 minutes.

[0023] Furthermore, the preparation method of the modified tourmaline powder is: weigh 5-6g of silane coupling agent KH-570 and pour it into 100mL of 80% ethanol aqueous solution, stir at a stirring speed of 300r / min for 3min, then add 15-20g of tourmaline powder, ultrasonically disperse at a frequency of 27-28kHz, and then place it at a temperature of 65°C to remove the solvent by rotary evaporation, and finally place it at a temperature of 48°C to dry for 3-5h, and the resulting modified tourmaline powder is obtained.

[0024] A method for preparing a stone crystal negative ion plate, the preparation method comprising:

[0025] 500 parts of modified polyvinyl chloride, 45-50 parts of modified bamboo fiber, 22-25 parts of composite flame retardant components, 50-60 parts of modified tourmaline powder, 60-70 parts of calcium carbonate, 30-35 parts of barium zinc stabilizer, 5-6 parts of oxidized wax, 5-6 parts of polyethylene wax, 9-10 parts of foaming agent and 15-20 parts of foaming regulator are weighed into a high-speed mixer, blended at a temperature of 120°C, cooled to 45°C, fed into an extruder and extruded through a die to obtain a stone crystal anion board.

[0026] Furthermore, the specific operation of blending in the preparation method is blending at a stirring speed of 600-800 r / min for 10 minutes.

[0027] Beneficial Effects

[0028] The present invention provides a stone crystal negative ion plate and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention uses acrylic rubber and ethylene-vinyl acetate copolymer to toughen and modify polyvinyl chloride, which can significantly improve the impact strength, toughness, processing performance and weather resistance of polyvinyl chloride while maintaining its own strength; acrylic rubber forms a network structure in polyvinyl chloride through its unique core-shell structure, which can generate multiple silver streaks when impacted and achieve silver streak passivation, thereby significantly improving the toughness of polyvinyl chloride; the addition of ethylene-vinyl acetate copolymer can improve the impact resistance of polyvinyl chloride, and on the basis of improving the melt fluidity of polyvinyl chloride, it can also enhance the weather resistance of polyvinyl chloride, thereby extending the outdoor service life of the plate prepared with polyvinyl chloride as raw material.

[0030] 2. The present invention uses titanium dioxide and copper oxide to coat bamboo fibers to prepare modified bamboo fibers, and then adds the fibers to modified polyvinyl chloride to prepare negative ion boards, which can enable the prepared negative ion boards to generate negative oxygen ions under light and have the ability to continuously generate negative oxygen ions; titanium dioxide is a material with photocatalytic activity, which can be stimulated to generate electrons and holes under the irradiation of ultraviolet light or visible light, so that it reacts with water molecules and oxygen in the air to generate hydroxyl free radicals and superoxide anions with strong oxidizing properties, which are then converted into negative oxygen ions; copper oxide and titanium dioxide can form a composite system, which can improve the overall photocatalytic efficiency through synergistic effects, thereby promoting the generation of negative oxygen ions.

[0031] 3. The present invention can make different flame retardants work together after compounding, so as to improve the flame retardant properties of the board; secondly, the tourmaline powder is modified by a silane coupling agent, which can improve the compatibility of the tourmaline powder and polyvinyl chloride, thereby preventing the tourmaline powder from agglomerating in the polyvinyl chloride; finally, the addition of a variety of additives can improve the stability of the prepared negative ion board, making it more suitable for use in different industries. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The present invention will be further described below in conjunction with the embodiments.

[0034] Example 1

[0035] A stone crystal negative ion plate of the present embodiment, the stone crystal negative ion plate is composed of the following components: modified polyvinyl chloride, modified bamboo fiber, composite flame retardant component, modified tourmaline powder, calcium carbonate, barium zinc stabilizer, oxidized wax, polyethylene wax, foaming agent and foaming regulator;

[0036] The modified polyvinyl chloride is obtained by toughening and modifying polyvinyl chloride with acrylic rubber and ethylene-vinyl acetate copolymer, wherein the preparation method of the modified polyvinyl chloride is as follows: 55g polyvinyl chloride, 6g acrylic rubber, 7g ethylene-vinyl acetate copolymer and 5g silane coupling agent KH-560 are weighed and poured into a high-speed mixer, and the mixture is blended at a temperature of 110°C and a stirring speed of 500r / min for 10min to obtain the modified polyvinyl chloride.

[0037] The modified bamboo fiber is prepared by coating the bamboo fiber with titanium dioxide and copper oxide, wherein the preparation steps of the modified bamboo fiber are as follows:

[0038] Step 1, weigh 2g of ammonium fluorotitanate and 2g of boric acid and disperse them in 150g of deionized water, stir them at a stirring speed of 500r / min for 30min, pour them into a reactor together with 18g of bamboo fiber, react at 90°C for 5h, cool to room temperature, then rinse with deionized water and dry at 45°C for 6h, and the obtained product is recorded as pre-modified bamboo fiber;

[0039] Step 2: Weigh 1g of polyvinyl pyrrolidone and 3g of glucose and add them to 25g of 0.1mol / L copper acetate solution. Stir at 300r / min for 1h, then pour into the reactor together with 18g of pre-modified bamboo fiber. React at 180°C for 2h and cool to room temperature. Then rinse with deionized water and dry at 45°C for 6h to obtain modified bamboo fiber.

[0040] The composite flame retardant component is prepared by mixing nano-hydroxy calcium stannate, aluminum oxide, zinc oxide and nano-silicon dioxide, wherein the preparation steps of nano-hydroxy calcium stannate are:

[0041] Step 1, weigh 1g of anhydrous calcium chloride, add it to a flask filled with 1L of deionized water, stir it at a stirring speed of 500r / min for 10min, and record the result as the calcium chloride component; weigh 3g of sodium stannate trihydrate, add it to a flask filled with 1L of deionized water, stir it at a stirring speed of 300r / min for 10min, and record the result as the sodium stannate hydrate component;

[0042] Step 2: Add 80 mL of triethylamine to 100 mL of the hydrated sodium stannate component, stir at a stirring speed of 300 r / min for 10 min, then add 100 mL of the calcium chloride component at a dropping rate of 1 drop / s, and let the reaction stand at room temperature for 3 hours. The resulting precipitated product is washed 3 times with anhydrous ethanol and deionized water respectively, and then freeze-dried for 12 hours to obtain nano-hydroxy calcium stannate.

[0043] The preparation method of the composite flame retardant component is as follows: nano-hydroxy calcium stannate, aluminum oxide, zinc oxide, nano-silicon dioxide and silane coupling agent KH-570 are weighed in a weight ratio of 3:2:1:2:1, poured into a ball mill for ball milling, and the composite flame retardant component is obtained after ball milling for 10 minutes.

[0044] The modified tourmaline powder is obtained by modifying the tourmaline powder with a silane coupling agent, wherein the preparation method of the modified tourmaline powder is as follows: 5 g of the silane coupling agent KH-570 is weighed and poured into 100 mL of an ethanol aqueous solution with a volume fraction of 80%, and 15 g of tourmaline powder is added after stirring at a stirring speed of 300 r / min for 3 minutes, and the mixture is ultrasonically dispersed at a frequency of 27 kHz, and then the solvent is removed by rotary evaporation at a temperature of 65° C., and finally the mixture is dried at a temperature of 48° C. for 3 hours to obtain the modified tourmaline powder.

[0045] A method for preparing a stone crystal negative ion plate, the preparation method comprising:

[0046] 500 parts of modified polyvinyl chloride, 45 parts of modified bamboo fiber, 22 parts of composite flame retardant component, 50 parts of modified tourmaline powder, 60 parts of calcium carbonate, 30 parts of barium zinc stabilizer, 5 parts of oxidized wax, 5 parts of polyethylene wax, 9 parts of foaming agent and 15 parts of foaming regulator are weighed into a high-speed mixer, mixed at a temperature of 120°C and a stirring speed of 600r / min for 10 minutes, then cooled to 45°C and sent to an extruder for extrusion through a die to obtain a stone crystal negative ion sheet.

[0047] Example 2

[0048] A stone crystal negative ion plate of the present embodiment, the stone crystal negative ion plate is composed of the following components: modified polyvinyl chloride, modified bamboo fiber, composite flame retardant component, modified tourmaline powder, calcium carbonate, barium zinc stabilizer, oxidized wax, polyethylene wax, foaming agent and foaming regulator;

[0049] The modified polyvinyl chloride is prepared by toughening and modifying polyvinyl chloride with acrylic rubber and ethylene-vinyl acetate copolymer, wherein the preparation method of the modified polyvinyl chloride is as follows: 60g polyvinyl chloride, 7g acrylic rubber, 8g ethylene-vinyl acetate copolymer and 8g silane coupling agent KH-560 are weighed and poured into a high-speed mixer, and the mixture is blended at a temperature of 120°C and a stirring speed of 600r / min for 10min to obtain the modified polyvinyl chloride.

[0050] The modified bamboo fiber is prepared by coating the bamboo fiber with titanium dioxide and copper oxide, wherein the preparation steps of the modified bamboo fiber are as follows:

[0051] Step 1, weigh 3g of ammonium fluorotitanate and 3g of boric acid and disperse them in 200g of deionized water, stir them at a stirring speed of 500r / min for 30min, pour them into a reactor together with 20g of bamboo fiber, react at 90°C for 5h, cool to room temperature, then rinse with deionized water and dry at 45°C for 6h, the obtained product is recorded as pre-modified bamboo fiber;

[0052] Step 2: Weigh 2g of polyvinyl pyrrolidone and 4g of glucose and add them to 30g of 0.1mol / L copper acetate solution. Stir at 300r / min for 1h, then pour into the reactor together with 20g of pre-modified bamboo fiber. React at 180°C for 2h and then cool to room temperature. Then rinse with deionized water and dry at 45°C for 6h to obtain modified bamboo fiber.

[0053] The composite flame retardant component is prepared by mixing nano-hydroxy calcium stannate, aluminum oxide, zinc oxide and nano-silicon dioxide, wherein the preparation steps of nano-hydroxy calcium stannate are:

[0054] Step 1, weigh 1g of anhydrous calcium chloride, add it to a flask filled with 1L of deionized water, stir it at a stirring speed of 500r / min for 10min, and record the result as the calcium chloride component; weigh 3g of sodium stannate trihydrate, add it to a flask filled with 1L of deionized water, stir it at a stirring speed of 300r / min for 10min, and record the result as the sodium stannate hydrate component;

[0055] Step 2: Add 90 mL of triethylamine to 100 mL of the hydrated sodium stannate component, stir at a stirring speed of 300 r / min for 10 min, then add 100 mL of the calcium chloride component at a dropping rate of 1 drop / s, and let the reaction stand at room temperature for 4 h. The resulting precipitated product is washed 3 times with anhydrous ethanol and deionized water respectively, and then freeze-dried for 12 h to obtain nano-hydroxy calcium stannate.

[0056] The preparation method of the composite flame retardant component is as follows: nano-hydroxy calcium stannate, aluminum oxide, zinc oxide, nano-silicon dioxide and silane coupling agent KH-570 are weighed in a weight ratio of 3:2:1:2:1, poured into a ball mill for ball milling, and the composite flame retardant component is obtained after ball milling for 10 minutes.

[0057] The modified tourmaline powder is obtained by modifying the tourmaline powder with a silane coupling agent, wherein the preparation method of the modified tourmaline powder is as follows: 6 g of silane coupling agent KH-570 is weighed and poured into 100 mL of ethanol aqueous solution with a volume fraction of 80%, and 20 g of tourmaline powder is added after stirring at a stirring speed of 300 r / min for 3 minutes, and the mixture is ultrasonically dispersed at a frequency of 28 kHz, and then the solvent is removed by rotary evaporation at a temperature of 65° C., and finally the mixture is dried at a temperature of 48° C. for 5 hours to obtain the modified tourmaline powder.

[0058] A method for preparing a stone crystal negative ion plate, the preparation method comprising:

[0059] 500 parts of modified polyvinyl chloride, 50 parts of modified bamboo fiber, 25 parts of composite flame retardant component, 60 parts of modified tourmaline powder, 70 parts of calcium carbonate, 35 parts of barium zinc stabilizer, 6 parts of oxidized wax, 6 parts of polyethylene wax, 10 parts of foaming agent and 20 parts of foaming regulator are weighed into a high-speed mixer, mixed at a temperature of 120°C and a stirring speed of 800r / min for 10 minutes, then cooled to 45°C and sent to an extruder for extrusion through a die to obtain a stone crystal negative ion sheet.

[0060] Example 3

[0061] A stone crystal negative ion plate of the present embodiment, the stone crystal negative ion plate is composed of the following components: modified polyvinyl chloride, modified bamboo fiber, composite flame retardant component, modified tourmaline powder, calcium carbonate, barium zinc stabilizer, oxidized wax, polyethylene wax, foaming agent and foaming regulator;

[0062] The modified polyvinyl chloride is prepared by toughening and modifying polyvinyl chloride with acrylic rubber and ethylene-vinyl acetate copolymer, wherein the preparation method of the modified polyvinyl chloride is as follows: 58g polyvinyl chloride, 7g acrylic rubber, 7g ethylene-vinyl acetate copolymer and 7g silane coupling agent KH-560 are weighed and poured into a high-speed mixer, and the mixture is blended at a temperature of 115°C and a stirring speed of 600r / min for 10min to obtain the modified polyvinyl chloride.

[0063] The modified bamboo fiber is prepared by coating the bamboo fiber with titanium dioxide and copper oxide, wherein the preparation steps of the modified bamboo fiber are as follows:

[0064] Step 1, weigh 3g of ammonium fluorotitanate and 2g of boric acid and disperse them in 180g of deionized water, stir them at a stirring speed of 500r / min for 30min, pour them into a reactor together with 19g of bamboo fiber, react at 90°C for 5h, cool to room temperature, then rinse with deionized water and dry at 45°C for 6h, the obtained product is recorded as pre-modified bamboo fiber;

[0065] Step 2: Weigh 2g of polyvinyl pyrrolidone and 4g of glucose and add them to 28g of 0.1mol / L copper acetate solution. Stir at 300r / min for 1h, then pour into the reactor together with 19g of pre-modified bamboo fiber. React at 180°C for 2h and then cool to room temperature. Then rinse with deionized water and dry at 45°C for 6h to obtain modified bamboo fiber.

[0066] The composite flame retardant component is prepared by mixing nano-hydroxy calcium stannate, aluminum oxide, zinc oxide and nano-silicon dioxide, wherein the preparation steps of nano-hydroxy calcium stannate are:

[0067] Step 1, weigh 1g of anhydrous calcium chloride, add it to a flask filled with 1L of deionized water, stir it at a stirring speed of 500r / min for 10min, and record the result as the calcium chloride component; weigh 3g of sodium stannate trihydrate, add it to a flask filled with 1L of deionized water, stir it at a stirring speed of 300r / min for 10min, and record the result as the sodium stannate hydrate component;

[0068] Step 2: Add 85 mL of triethylamine to 100 mL of the hydrated sodium stannate component, stir at a stirring speed of 300 r / min for 10 min, then add 100 mL of the calcium chloride component at a dropping rate of 1 drop / s, and let the reaction stand at room temperature for 4 h. The resulting precipitated product is washed 3 times with anhydrous ethanol and deionized water respectively, and then freeze-dried for 12 h to obtain nano-hydroxy calcium stannate.

[0069] The preparation method of the composite flame retardant component is as follows: nano-hydroxy calcium stannate, aluminum oxide, zinc oxide, nano-silicon dioxide and silane coupling agent KH-570 are weighed in a weight ratio of 3:2:1:2:1, poured into a ball mill for ball milling, and the composite flame retardant component is obtained after ball milling for 10 minutes.

[0070] The modified tourmaline powder is obtained by modifying the tourmaline powder with a silane coupling agent, wherein the preparation method of the modified tourmaline powder is as follows: 6 g of silane coupling agent KH-570 is weighed and poured into 100 mL of 80% ethanol aqueous solution by volume, and 18 g of tourmaline powder is added after stirring at a stirring speed of 300 r / min for 3 minutes, and the mixture is ultrasonically dispersed at a frequency of 28 kHz, and then the solvent is removed by rotary evaporation at a temperature of 65° C., and finally the mixture is dried at a temperature of 48° C. for 4 hours to obtain the modified tourmaline powder.

[0071] A method for preparing a stone crystal negative ion plate, the preparation method comprising:

[0072] 500 parts of modified polyvinyl chloride, 48 parts of modified bamboo fiber, 23 parts of composite flame retardant component, 55 parts of modified tourmaline powder, 65 parts of calcium carbonate, 33 parts of barium zinc stabilizer, 6 parts of oxidized wax, 5 parts of polyethylene wax, 10 parts of foaming agent and 18 parts of foaming regulator were weighed by weight and poured into a high-speed mixer. The mixture was blended at a temperature of 120°C and a stirring speed of 700 r / min for 10 minutes, then cooled to 45°C and fed into an extruder to be extruded through a die to obtain a stone crystal negative ion sheet.

[0073] Comparative Example 1

[0074] The stone crystal negative ion plate and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the modified polyvinyl chloride in Example 1 is replaced with unmodified polyvinyl chloride.

[0075] Comparative Example 2

[0076] The stone crystal negative ion plate and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 2, the modified bamboo fiber in Example 1 is replaced with unmodified bamboo fiber.

[0077] Comparative Example 3

[0078] The stone crystal anion plate and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 3, the composite flame retardant component in Example 1 is replaced with the nano-calcium hydroxystannate in Example 1.

[0079] Comparative Example 4

[0080] The stone crystal negative ion plate and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 4, the modified tourmaline powder in Example 1 is replaced with unmodified tourmaline powder.

[0081] Performance Testing

[0082] The stone crystal anion plates prepared in Examples 1-3 and Comparative Examples 1-4 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-4 is tested. The specific testing methods and test items are as follows:

[0083] 1. The tensile strength of Examples 1-3 and Comparative Examples 1-4 was tested according to the standard of GB / T1040.3-2006. The specimens were cut into dumbbell-shaped standard specimens. The tensile rate was 50 mm / min. The obtained data are recorded in Table 1.

[0084] 2. The bending strength of Examples 1-3 and Comparative Examples 1-4 was tested according to the standard of GB / T9341-2008, and the obtained data are recorded in Table 1.

[0085] 3. According to the limiting oxygen index test standard of GB / T2406-1993, the limiting oxygen index instrument was used to test the examples 1-3 and comparative examples 1-4. The oxygen concentration in the combustion chamber was changed by adjusting the content of oxygen and nitrogen to test the self-extinguishing oxygen concentration of the stone crystal negative ion plate. The obtained data are recorded in Table 1.

[0086] 4. The notched impact strength of Examples 1-3 and Comparative Examples 1-4 was tested using the standard of GB / T1843-2008. The cantilever beam mode was used and the pendulum impact energy was 4.4 J.

[0087] The impact strength at room temperature was tested and the obtained data are recorded in Table 1.

[0088] 5. Cut the stone crystal anion plates prepared in Examples 1-3 and Comparative Examples 1-4 into 3cm×3cm×3cm sizes, and then place them in a 50cm×50cm×50cm sealed device. A light source with a wavelength of 365nm and a light intensity of about 1.5mW / cm 2 UV lamp, using AIC1000 negative oxygen ion detector, with a resolution of 10 / cm 3 ; Initially, the negative oxygen ion detector must be reset to zero, and the value before the test must remain unchanged within 5 seconds. Then turn on the ultraviolet lamp to irradiate the sample. The test of ultraviolet light irradiation to release negative oxygen ions lasts for 120 minutes. Record the value of the negative oxygen ion detector in the device every 10 minutes, and the obtained data is recorded in the table below.

[0089] Table 1

[0090]

[0091] Table 2

[0092]

[0093] It can be seen from the data in Table 1 that the mechanical properties of the stone crystal anion plate of Examples 1-3 are significantly higher than those of Comparative Example 1, indicating that the modified polyvinyl chloride added to the stone crystal anion plate can enhance the mechanical properties; the limiting oxygen index of Examples 1-3 is significantly higher than that of Comparative Example 3, indicating that the composite flame retardant component formed by compounding multiple flame retardants can improve the flame retardant properties of the plate to a greater extent than nano calcium hydroxystannate.

[0094] It can be seen from the data in Table 2 that the amount of negative oxygen ion released by the stone crystal negative ion plate of Examples 1-3 is significantly higher than that of Comparative Example 2 and Comparative Example 4, indicating that the addition of modified bamboo fiber and modified tourmaline powder can improve the speed of the stone crystal negative ion plate in releasing negative oxygen ions, and can make it have better negative oxygen ion release capacity.

[0095] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0096] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A stone crystal negative ion plate, characterized in that: The stone crystal negative ion plate is composed of the following components: modified polyvinyl chloride, modified bamboo fiber, composite flame retardant component, modified tourmaline powder, calcium carbonate, barium zinc stabilizer, oxidized wax, polyethylene wax, foaming agent and foaming regulator; The modified polyvinyl chloride is prepared by toughening and modifying polyvinyl chloride with acrylic rubber and ethylene-vinyl acetate copolymer; The modified bamboo fiber is prepared by coating the bamboo fiber with titanium dioxide and copper oxide; The composite flame retardant component is prepared by mixing nanometer calcium hydroxystannate, aluminum oxide, zinc oxide and nanometer silicon dioxide; The modified tourmaline powder is obtained by modifying tourmaline powder with a silane coupling agent; The preparation method of the modified polyvinyl chloride is as follows: 55-60g of polyvinyl chloride, 6-7g of acrylic rubber, 7-8g of ethylene-vinyl acetate copolymer and 5-8g of silane coupling agent KH-560 are weighed and poured into a high-speed mixer, and mixed at a temperature of 110-120°C and a stirring speed of 500-600r / min for 10min to obtain the modified polyvinyl chloride; The preparation method of the composite flame retardant component is as follows: weigh nano-hydroxy calcium stannate, aluminum oxide, zinc oxide, nano-silicon dioxide and silane coupling agent KH-570 according to a weight ratio of 3:2:1:2:1, pour them into a ball mill for ball milling, and the composite flame retardant component is obtained after ball milling for 10 minutes; The preparation method of the modified tourmaline powder is as follows: weigh 5-6g of silane coupling agent KH-570 and pour it into 100mL of ethanol aqueous solution with a volume fraction of 80%, stir at a stirring speed of 300r / min for 3min, then add 15-20g of tourmaline powder, ultrasonically disperse at a frequency of 27-28kHz, then place it at a temperature of 65°C to remove the solvent by rotary evaporation, and finally place it at a temperature of 48°C to dry for 3-5h, so as to obtain the modified tourmaline powder.

2. The stone crystal negative ion plate according to claim 1, characterized in that: The preparation steps of the modified bamboo fiber are: Step 1, weigh 2-3g of ammonium fluorotitanate and 2-3g of boric acid and disperse them in 150-200g of deionized water, stir and dissolve them, pour them into a reaction kettle together with 18-20g of bamboo fiber, react at 90°C for 5h, cool to room temperature, then rinse with deionized water and dry at 45°C for 6h, the obtained product is recorded as pre-modified bamboo fiber; Step 2: Weigh 1-2g of polyvinyl pyrrolidone and 3-4g of glucose and add them to 25-30g of copper acetate solution. After stirring and dispersing, pour them into the reactor together with 18-20g of pre-modified bamboo fiber. React at 180°C for 2h and then cool to room temperature. Then rinse with deionized water and dry at 45°C for 6h to obtain modified bamboo fiber.

3. The stone crystal negative ion plate according to claim 2, characterized in that: The specific operation of stirring and dissolving in step 1 is stirring at a stirring speed of 500 r / min for 30 minutes, the concentration of the copper acetate solution in step 2 is 0.1 mol / L, and the specific operation of stirring and dispersing in step 2 is stirring at a stirring speed of 300 r / min for 1 hour.

4. The stone crystal negative ion plate according to claim 1, characterized in that: The preparation steps of the nano calcium hydroxystannate are: Step 1, weigh 1g of anhydrous calcium chloride, add it into a flask filled with 1L of deionized water, stir until dissolved, and record the result as the calcium chloride component; weigh 3g of sodium stannate trihydrate, add it into a flask filled with 1L of deionized water, stir until dissolved, and record the result as the sodium stannate hydrate component; Step 2: Add 80-90 mL of triethylamine to 100 mL of the hydrated sodium stannate component, mix well, then add 100 mL of the calcium chloride component at a rate of 1 drop / s, and let the reaction stand at room temperature for 3-4 hours. The resulting precipitate product is washed 3 times with anhydrous ethanol and deionized water, then freeze-dried for 12 hours to obtain nano-hydroxy calcium stannate.

5. The stone crystal negative ion plate according to claim 4, characterized in that: The specific operation of stirring until dissolved in step 1 is stirring at a stirring speed of 500 r / min for 10 min, and the specific operation of mixing evenly in step 2 is stirring at a stirring speed of 300 r / min for 10 min.

6. A method for preparing a stone crystal negative ion plate according to any one of claims 1 to 5, characterized in that: The preparation method is: 500 parts of modified polyvinyl chloride, 45-50 parts of modified bamboo fiber, 22-25 parts of composite flame retardant components, 50-60 parts of modified tourmaline powder, 60-70 parts of calcium carbonate, 30-35 parts of barium zinc stabilizer, 5-6 parts of oxidized wax, 5-6 parts of polyethylene wax, 9-10 parts of foaming agent and 15-20 parts of foaming regulator are weighed into a high-speed mixer, blended at a temperature of 120°C, cooled to 45°C, fed into an extruder and extruded through a die to obtain a stone crystal anion board.

7. The method for preparing a stone crystal negative ion plate according to claim 6, characterized in that: The specific operation of blending in the preparation method is blending at a stirring speed of 600-800 r / min for 10 minutes.

Citation Information

Patent Citations

  • Preparation of multifunctional wood-plastic composite material

    CN101033317A

  • Wood-based material capable of releasing negative oxygen ions under ultraviolet irradiation and preparation method of wood-based material

    CN105799020A